2020
DOI: 10.3389/fphar.2020.00449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early and Delayed Antiretroviral Therapy on Plasma Anti-CD4 Autoreactive IgG and Its Association With CD4+ T-Cell Recovery in Acute HIV-Infected Individuals

Abstract: Background: Plasma levels of anti-CD4 autoantibodies are increased in chronically HIVinfected patients and inversely correlated with CD4 + T-cell recovery under viralsuppressive antiretroviral therapy (ART). However, it remains unknown the effect of early ART on plasma anti-CD4 autoantibody levels in acute HIV infection (AHI).Methods: In this cohort study, we evaluated the effect of early and delayed initiation of ART on plasma anti-CD4 autoantibody levels in AHI individuals (n = 90). Blood samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
7
1
Order By: Relevance
“…We also observed a similar result that the negative association trends between the frequency of IL-21 + ICOS + cTfh cells and CD4 + T cell count in both acute and chronic HIV-1 infection stage ( Figure 5A ). Our previous study demonstrated that higher level of anti-CD4 antibody is responsible for CD4 + T cell depletion during HIV-1 acute infection ( 70 ). Therefore, we hypothesize that the overactivation of cTfh cells with high ICOS level and more IL-21 secretion by ICOS + cTfh cells induces the excessive anti-CD4 antibody generation, thereby promoting the progression of CD4 + T cell loss even the induction of idiopathic CD4 lymphopenia ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a similar result that the negative association trends between the frequency of IL-21 + ICOS + cTfh cells and CD4 + T cell count in both acute and chronic HIV-1 infection stage ( Figure 5A ). Our previous study demonstrated that higher level of anti-CD4 antibody is responsible for CD4 + T cell depletion during HIV-1 acute infection ( 70 ). Therefore, we hypothesize that the overactivation of cTfh cells with high ICOS level and more IL-21 secretion by ICOS + cTfh cells induces the excessive anti-CD4 antibody generation, thereby promoting the progression of CD4 + T cell loss even the induction of idiopathic CD4 lymphopenia ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of CD4 lymphocytes occurs in the first 2 years after starting ART and is associated with age and the pre-existing degree of HIV-1-related immunodeficiency, so long-term exposure to HIV-1 infection damages the immune system in ways that are difficult to correct due to exhaustion 32 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Other observation and randomized cohort studies also showed that baseline HIV viral load > 500 000 copies/mL is associated with virological failure, leading to immune failure [40–44]. From the perspective of clinical relevance, these results also highlighted the benefits of the policy of ‘early detection and early treatment’ in the immune restoration [45]. Further studies are needed to verify the potential mechanism underlying this phenomenon.…”
Section: Discussionmentioning
confidence: 83%